DAMPAK NOMOPHOBIA GADGET TERHADAP KEHIDUPAN SOSIAL PADA REMAJA DI KOTA PEKANBARU - Yosua Demart Saragih Saragih; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was carried out in sub-districts in accordance with Nomophobia residences in Pekanbaru City. The purpose of this study was to find out the social life of Nomophobia adolescents in the social environment of the community and to find out the positive and negative effects of the Gadget for teenagers. The subjects in this study amounted to 12 people, of which 3 core informants and 9 supporting informants. Writing uses qualitative descriptive methods and data analyzed qualitatively and uses subject taking techniques with the Snowball Samply method. Data instruments are in-depth interviews, observation and documentation. From the results of research conducted by researchers found that addicts who are addicted to or Nomophobia Gadgets have a social life that leads to a negative impact and a decreased level of achievement is due to not being able to divide the time between playing gadgets and the responsibility of students and children in the household. The essence of this study is more negative for adolescents who are addicted to gadgets compared to the positive effects generated by teenagers nomophobia. Keywords : Teenagers, Nomophobia, Social Life, Gadget